NILAI SEJARAH DALAM AL-QURAN - M. Dalhari (UIN Raden Mas Said Surakarta, 2014)
Koran (Al-Quran) is not the book of history. The fact is ittells the reader about chronological events in a story or set of histories.The article describes the views from Koran about the history andexplains about the historical problems in Koran‟s views. The moralfactor has the special portions in Koran. This factor can perpetuate thenation of being destroyed. It is accepted by the Moslem scholars(ulama‟) that the moral factor gives the direct implication in practicaldaily lives, as the parameter of personality, and as the behavior of ahuman in a nation or a community. The histories revealed by Koranare the „living history‟ and the events that involve the readers to haveconversations and participate in dialogues.